An Examination of the Factor Structure of the Trauma Inventory for Partners of Sex Addicts (TIPSA). Issue 1 (2nd January 2018) - Vogeler, Heidi A.; Fischer, Lane; Sudweeks, Richard R.; Skinner, Kevin B.
ABSTRACT: The Trauma Inventory for Partners of Sex Addicts (TIPSA) was hypothesized to have a latent factor structure that mirrors the core criteria for Post-traumatic Stress Disorder (PTSD). Data were gathered from 3, 199 self-selected respondents, and confirmatory factor analysis (CFA) was performed in order to substantiate the hypothesized structure. Several modifications were made to the model, based on factor loadings and modification indices, in order to improve goodness-of-fit. In addition to the hypothesized model, 3 other factor models were also examined. Recommendations for revision of items contained in the TIPSA, as well as evaluation of additional psychometric properties, are also included.